Dopaminergic nuclei in the chick midbrain express serotonin receptor subfamily genes - Fujita, Toshiyuki; Aoki, Naoya; Mori, Chihiro; Serizawa, Shouta; Kihara-Negishi, Fumiko; Homma, Koichi J.; Yamaguchi, Shinji (Frontiers in Physiology, 2022)
Serotonin (5-hydroxytryptamine, 5-HT) is a phylogenetically conserved modulator of numerous aspects of neural functions. Serotonergic neurons in the dorsal and median raphe nucleus provide ascending innervation to the entire forebrain and midbrain. Another important neural modulatory system exists in the midbrain, the dopaminergic system, which is associated to reward processing and motivation control. Dopaminergic neurons are distributed and clustered in the brain, classically designated as groups A8-A16. Among them, groups A8-A10 associated with reward processing and motivation control are located in the midbrain and projected to the forebrain. Recently, midbrain dopaminergic neurons were shown to be innervated by serotonergic neurons and modulated by 5-HT, with the crosstalk between serotonergic and dopaminergic systems attracting increased attention. In birds, previous studies revealed that midbrain dopaminergic neurons are located in the A8-A10 homologous clusters. However, the detailed distribution of dopaminergic neurons and the crosstalk between serotonergic and dopaminergic systems in the bird are poorly understood. To improve the understanding of the regulation of the dopaminergic by the serotonergic system, we performed in situ hybridization in the chick brainstem. We prepared RNA probes for chick orthologues of dopaminergic neuron-related genes; tyrosine hydroxylase (TH) and dopa decarboxylase (DDC), noradrenalin related genes; noradrenalin transporter (NAT) and dopamine beta-hydroxylase (DBH), and serotonin receptor genes; 5-HTR1A, 5-HTR1B, 5-HTR1D, 5-HTR1E, 5-HTR1F, 5-HTR2A, 5-HTR2B, 5-HTR2C, 5-HTR3A, 5-HTR4, 5-HTR5A, and 5-HTR7. We confirmed that the expression of TH and NAT was well matched in all chick dopaminergic nuclei examined. This supported that the compensation of the function of DAT by NAT is a general property of avian dopaminergic neurons. Furthermore, we showed that 5-HTR1A and 5-HTR1B were expressed in midbrain dopaminergic nuclei, suggesting the serotonergic regulation of the dopaminergic system via these receptors in chicks. Our findings will help us understand the interactions between the dopaminergic and serotonergic systems in birds at the molecular level.